2009
DOI: 10.1590/s0366-69132009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of the red-color overglazes on the Kakiemon-style porcelains produced in the later 17th century by means of X-ray diffraction (I)

Abstract: Kakiemon-style porcelains produced at Arita areas (SAGA) in Kyushu Island are famous Japanese porcelains. The porcelain-techniques creating its elegant and bright red-color underglaze and overglaze were found and developed in 1650's (early Edo period) first by Kakiemon kiln. Red-color overglaze and transparent glaze of the Kakiemon-style porcelains have been investigated by means of X-ray diffraction using synchrotron radiation. The results suggest that the red-color brightness is mainly induced by micro-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…At the present, many Japanese celadon potters thought that fine air-bubbles in the celadon glaze contribute to a diffused reflection of blue-green light. Recently, we have studied the correlation between the red-colored brightness and the structural and electronic properties for the overglaze of the HIZEN colored porcelains, which were produced at Arita areas from the 17 th to 18 th century, by means of X-ray diffraction (XRD) and X-ray absorption spectrum (XAS), using synchrotron radiation [17][18][19]. In this paper, we study the geographical and historical correlations among the glaze-colors of the HIZEN celadons produced at Aita and Imari areas in the Edo period.…”
Section: Hidakamentioning
confidence: 99%
“…At the present, many Japanese celadon potters thought that fine air-bubbles in the celadon glaze contribute to a diffused reflection of blue-green light. Recently, we have studied the correlation between the red-colored brightness and the structural and electronic properties for the overglaze of the HIZEN colored porcelains, which were produced at Arita areas from the 17 th to 18 th century, by means of X-ray diffraction (XRD) and X-ray absorption spectrum (XAS), using synchrotron radiation [17][18][19]. In this paper, we study the geographical and historical correlations among the glaze-colors of the HIZEN celadons produced at Aita and Imari areas in the Edo period.…”
Section: Hidakamentioning
confidence: 99%
“…In the early 18th century, a high-quality red pigment (Fukiya bengala) was developed in Japan and used by pottery producers throughout Japan, such as in Arita, Kutani, and Kyoto. However, manufacturing of Fukiya bengala was prohibited by an antipollution law in 1970, eliminating this pigment from the market. Recently, we analyzed existing Fukiya bengala in detail and found that its main component is fine hematite particles containing 1 mol % Al .…”
Section: Introductionmentioning
confidence: 99%
“…Here we define “high quality”, “beautiful”, or “vivid” akae as akae with high L *, a *, and b * values on the CIE 1976 color space . For example, Fukiya bengala, a red pigment produced in Japan in the 18th century, has values of L * = 41.6, a * = 34.6, and b * = 27.5 . Then, similar and slightly higher values are considered to be “high quality”.…”
Section: Introductionmentioning
confidence: 99%
“…Although leaded glass frit with low melting points is conventionally used in traditional akae porcelain, the use of glass frit containing lead is now regulated owing to concerns for human health and the environment. In addition, the high-quality red pigment Fukiya bengala, ,− which had the largest market share in Japan, went out of use when antipollution laws came into effect in the 1970s. The porcelain industry has since been seeking new lead-free frit and high-quality hematite pigments.…”
Section: Introductionmentioning
confidence: 99%